KEPUTUSAN PEMBELIAN MELALUI ONLINE DITINJAU DARI KEMUDAHAN, PROMOSI, KEPERCAYAAN, DAN KUALITAS PRODUK PADA BATIK GUNAWAN DI SURAKARTA - Istibsyaroh Wulandari; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2021)
Online purchasing decisions by buyers of batik products can be made possible because of the convenience, promotion, trust and quality of the product at Batik Gunawan in Surakarta. In general, the purpose of this study is to analyze consumer purchasing decisions through online media in terms of convenience, promotion, trustworthiness, and product quality. This research is a type of quantitative descriptive research by taking a sample from a population using a questionnaire as a tool for data collection in the form of numbers and used to test predetermined hypotheses. The study population was all online customers of Batik Gunawan Surakarta with a total sampling technique, a total sample of 67 research samples was obtained during 2020. The data analysis technique used multiple linear regression, F test, test, and coefficient of determination. The results showed that there was an effect both simultaneously and partially, namely the effect of convenience, promotion, trustworthiness, and product quality simultaneously on online purchasing decisions at Batik Gunawan in Surakarta. Keywords: purchase decision, online, ease of promotion, trustworthiness, product quality.